Meningkatkan Skill dan Mengubah Pandangan Siswa terhadap Pembelajaran Bahasa Inggris Melalui Lagu dan Games - Wahab, Isnaeni; Tanasy, Novalia; Nuraeni, Nuraeni; Aisyah, Sitti; Fachrunnisa, Nurul; Astri, Zul (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2024)
It is crucial to start teaching English to children at a young age because of how important it is to learn it. In practice, English is not an easy language to teach to elementary school students. There are several main reasons why English is difficult to teach, the first is that English words and sentences are difficult to pronounce because they are written and pronounced differently. In addition, the lack of teacher skills in terms of mastering teaching techniques and methods makes students less interested in learning English. The problems faced by children in Bawasalo Village are the lack of mastery of vocabulary and correct pronunciation so that they have low English quality. The purpose of this service is to provide English language training through songs and games for children in Bawasalo Village, Maros Regency, South Sulawesi. The method of implementing this service is in the form of English song pronunciation and games that are suitable for elementary school children. The results of this activity show that children are more enthusiastic about learning English through games and songs. In fact, children can also easily master new vocabulary and good pronunciation